Randić index and information. Issue 3 (1st December 2018) - Gutman, Ivan; Furtula, Boris; Katanić, Vladimir
Abstract: The Randić index R G is one of the classical graph-based molecular structure descriptors that found countless applications in chemistry and pharmacology. The mathematical background of this index is also well elaborated. We now point out a hitherto unnoticed feature of R G, namely its connection with the degree-based information content of a (molecular) graph. This connection is based on the linear correlation between R G and the logarithm of the multiplicative version of the Randić index.